MEMBANGUN BUDAYA 3R DALAM MANAGEMEN SAMPAH MELALUI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA DAN PROJEK PELAJAR RAHMATAN LIL ALAMIN (P5P2RLA) - Anny Wahyuningsih (UNZAH Genggong, 2022)
This study aims to describe the strengthening of the character (profile) of Pancasila students through the Pancasila Student Profile and Lil Alamin Student Profile Projects (P5P2RLA). The research was conducted at MAN 2 PROBOLINGGO CITY. The methods used in this research are observation, documentation review, and interviews. The results of the analysis show that one of the scopes of implementing the independent curriculum is strengthening the profile of Pancasila students. In KMA no 347 of 2022 concerning Implementation of the Independent Curriculum in Madrasas it is stated that strengthening the profile of Pancasila students in madrasas is projected on 2 (two) aspects, namely the Profile of Pancasila Students and the Profile of Lil Alamin Students (P5P2RLA). As a pilot madrasa set by the Director General of Islamic Education, MAN 2 Probolinggo City must also carry out a project to strengthen the profile of Pancasila students. and students of rohmatan lil alamin. The application of the Pancasila student profile can be carried out through school culture, intra-curricular learning, co-curricular and extra-curricular activities which focus on building character and abilities that are built in daily life and lived in each individual. The implications of the research show that strengthening the character (profile) of Pancasila students can be done through classroom learning. Keywords: Pancasila Student Profile Project, Lil Alamin Student Profile (P5P2RLA), Character Education